Alternative splicing level related to intron size and organism complexity - Pengcheng Yang (BMC, 2021)
Abstract Background Alternative splicing is the process of selecting different combinations of splice sites to produce variably spliced mRNAs. However, the relationships between alternative splicing prevalence and level (ASP/L) and variations of intron size and organism complexity (OC) remain vague. Here, we developed a robust protocol to analyze the relationships between ASP/L and variations of intron size and OC. Approximately 8 Tb raw RNA-Seq data from 37 eumetazoan species were divided into three sets of species based on variations in intron size and OC. Results We found a strong positive correlation between ASP/L and OC, but no correlation between ASP/L and intron size across species. Surprisingly, ASP/L displayed a positive correlation with mean intron size of genes within individual genomes. Moreover, our results revealed that four ASP/L-related pathways contributed to the differences in ASP/L that were associated with OC. In particular, the spliceosome pathway displayed distinct genomic features, such as the highest gene expression level, conservation level, and fraction of disordered regions. Interestingly, lower or no obvious correlations were observed among these genomic features. Conclusions The positive correlation between ASP/L and OC ubiquitously exists in eukaryotes, and this correlation is not affected by the mean intron size of these species. ASP/L-related splicing factors may play an important role in the evolution of OC.